Shapeshifting fields: Mao Chenyu's rural media ecology. Issue 2 (4th May 2019) - Shaffer, Benny
Abstract: This paper examines the recent moving image work of artist, researcher, and rice farmer Mao Chenyu, who has spent over a decade making ethnographically inflected documentary work in his village outside of Yueyang in Hunan Province. With his innovative approaches, which combine the visual idioms of the essay film, found footage collage, autodidactic philosophical reflections, and observational cinema, his work provokes a conceptual reevaluation of rural life and agrarian labor among China's peasantry. Mao is the founder of Paddy Film Farm, a grassroots operation that serves as both an independent film studio, as well as a cottage industry for the production of organic rice and strong liquor. Through his on-the-ground ethnographic research, he self-identifies as a "native anthropologist, " and explores new modes of knowledge production and experimental storytelling that are displayed in contexts ranging from China's small circuit of underground film screenings to alternative art spaces and state-sponsored museums. In this paper, I draw on close readings of two of Mao's films, I Have What? Chinese Peasants War: The Rhetoric to Justice (2014) and Cloud Explosion: Dongting Lake and the Death of Its Symbols (2015); multimedia installations at the 2016 Shanghai Biennial and a recent solo exhibition at A + Contemporary in Shanghai's M50 Art District; and finally, on an analysis of my own ethnographic research (participant-observation field notes, informal interviews, textual analysis, and curated screenings and discussions) conducted with the artist between Shanghai and Yueyang from 2015 to 2017.